Characterizing corrosion properties of carbon steel affected by high-power laser cleaning. (8th March 2021) - Zhuang, Shusen; Kainuma, Shigenobu; Yang, Muye; Haraguchi, Manabu; Asano, Takahiro
Highlight: Iron oxide and gradient microstructures were formed on the surface of steel plates treated by rotating high-power CW laser. The oxidation state and content of iron oxide increased with laser power density and interaction time. Improving corrosion resistance of laser-treated steel plates mainly attributed to the formation of iron oxide. Calculated peak temperature during laser irradiation explained the MZ depth and surface morphology. Abstract: A high-power CW laser equipment was used to irradiate bare carbon steel plates to evaluate the effects of laser surface cleaning on the corrosion properties of the base metal. Different laser processing parameters were adopted, representing lower to higher laser ablation effects. The surface oxide content was analyzed using XRD and SEM-EDX, the microstructure was observed under optical microscopy, and the corrosion properties of the specimens were evaluated using electrochemical tests. The results demonstrated that the CW laser-treated steel plates possessed better corrosion resistance than the unirradiated steel plates. Higher laser power density and interaction time result in denser iron oxide formed on the steel surface, which is the main reason for the improved corrosion resistance. Layers with modified microstructures are present in all laser-treated steel plates. The laser ablation effects and gradient microstructures can be well described by the theoretical peak temperature distribution. The laser surface cleaning technique for steel structures is thereby confirmed to have a positive impact on the corrosion properties of the base metal.